The diversity of AMPA receptor inhibition mechanisms among amidine-containing compounds - Zhigulin, Arseniy S.; Dron, Mikhail Y.; Barygin, Oleg I.; Tikhonov, Denis B. (Frontiers in Pharmacology, 2024)
Amidine-containing compounds are primarily known as antiprotozoal agents (pentamidine, diminazene, furamidine) or as serine protease inhibitors (nafamostat, sepimostat, camostat, gabexate). DAPI is widely recognized as a fluorescent DNA stain. Recently, it has been shown that these compounds also act as NMDA receptor inhibitors. In this study, we examined the activity of these compounds and analyzed the mechanisms of action in relation to another important class of ionotropic glutamate receptorscalcium-permeable AMPA receptors (CP-AMPARs) and calcium-impermeable AMPA receptors (CI-AMPARs)using the whole-cell patch-clamp method on isolated male Wistar rat brain neurons. Gabexate and camostat were found to be inactive. Other compounds preferentially inhibited calcium-permeable AMPA receptors with IC 50 values of 30-60 µM. DAPI and furamidine were also active against CI-AMPARs with IC 50 s of 50-60 µM, while others showed poor activity. All active compounds acted as channel blockers, which are able for permeating into the cytoplasm on both CP-and CI-AMPARs. Specifically, sepimostat showed trapping in the closed CP-AMPAR channel.Furamidine and DAPI demonstrated a voltage-independent action on CI-AMPARs, indicating binding to an additional superficial site. While the majority of compounds inhibited glutamate-activated steadystate currents as well as kainate-activated currents on CI-AMPARs, pentamidine significantly potentiated glutamate-induced steady-state responses. The potentiating effect of pentamidine resembles the action of the positive allosteric modulator cyclothiazide although the exact binding site remains unclear. Thus, this study, together with our previous research on NMDA receptors, provides a comprehensive overview of this novel group of ionotropic glutamate receptors inhibitors with a complex pharmacological profile, remarkable diversity of effects and mechanisms of action.